Implementing risk management to reduce injuries in the U.S. Fire Service. (February 2017) - Pollack, Keshia M.; Poplin, Gerald S.; Griffin, Stephanie; Peate, Wayne; Nash, Virginia; Nied, Ed; Gulotta, John; Burgess, Jefferey L.
Abstract: Introduction: Risk management, a proactive process to identify and mitigate potential injury risks and implement control strategies, was used to reduce the risk of occupational injury in a fire department. The objective of this research was to study the implementation of the risk management process for future replication. A second objective was to document changes in fire personnel's knowledge, attitudes, and behaviors related to the selected control strategies that were implemented as part of the risk management process. Method: A number of control strategies identified through the risk management process were implemented over a 2-year period beginning in January 2011. Approximately 450 fire personnel completed each of the three cross-sectional surveys that were administered throughout the implementation periods. Fire personnel were asked about their awareness, knowledge, and use of the control strategies. Results: Fire personnel were generally aware of the control strategies that were implemented. Visual reminders (e.g., signage) were noted as effective by fire personnel who noticed them. Barriers to use of specific control strategies such as new procedures on the fireground or new lifting equipment for patient transfer included lack of knowledge of the new protocols, lack of awareness/access to/availability of the new equipment, and limited training on its use. Implementation challenges were noted, which limited self-reported adherence to the control strategies. Conclusions: Fire personnel generally recognized the potential for various control strategies to manage risk and improve their health and safety; however, implementation challenges limited the effectiveness of certain control strategies. The study findings support the importance of effective implementation to achieve the desired impacts of control strategies for improving health and safety. Practical applications: Employees must be aware of, have knowledge about, and receive training in safety and health interventions in order to adopt desired behaviors. Highlights: Proactive risk management helps identify and control potential injury risks. We partnered with a metropolitan fire department to apply a risk management approach. Fire personnel were aware of many control strategies that were implemented. Implementation challenges limited the impact of these control strategies. Knowledge, awareness, and training are key for effective implementation of control strategies.